Decrystallization with high current pulses technique for capacity restoration of industrial nickel-cadmium battery - M. P. Martin; Asmarashid Ponniran; R. A. Rahman; N. S. M. Ibrahim; A. Eahambram; M. H. Aziz; A. M. Yassin (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
The process of crystallization occurred due to the process of charging and discharging during the usage of the Nickel-Cadmium (Ni-Cd) battery where crystalline formed on the surface of the battery plate. This situation causes the impedance of the Ni-Cd battery increased and contribute to the increment of the battery temperature and battery impedance. High battery temperature will cause the performance of Ni-Cd battery deteriorates. Therefore, this study is investigated on the performance of industrial Ni-Cd battery during the process of crystallization and de-crystallization with high current pulses. By this technique, it is capable to break the formed crystalline to recover back the capacity loss and enhanced the performance of Ni-Cd battery. Therefore, the study results shown that the life cycles and capacity of the Ni-Cd battery increased up to 41% of its capacity after the de-crystallization take place by injecting high current pulses. Consequently, the life span of the Nickel-Cadmium battery enhanced, and the battery is revived.